Front Cover: Chemical Modification of the sp‐Hybridized Carbon Atoms of Graphdiyne by Using Organic Sulfur (Chem. Eur. J. 22/2019). Issue 22 (15th March 2019) - Yang, Ze; Cui, Weiwei; Wang, Kun; Song, Yuwei; Zhao, Fuhua; Wang, Ning; Long, Yunze; Wang, Huanlei; Huang, Changshui
Abstract : Benzyl disulfide was first applied to the chemical modification of the sp‐hybridized carbon atoms in graphdiyne. All the decorated sulfur atoms are in the single form of C−S−C bonds, providing more heteroatomic defects and active sites to improve the electrochemical properties. Compared with pristine graphdiyne, the electrodes based on sulfur‐modified graphdiyne exhibit higher reversible capacities and superior cycling stability, indicating that chemical modification with benzyl disulfide is an efficient approach for further improving the electrochemical performance of graphdiyne‐based materials. More information can be found in the Communication by C. Huang et al. on page 5643 .